1996
DOI: 10.1002/eji.1830261130
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid DNA and protein vaccination of mice to the outer surface protein A of Borrelia burgdorferi leads to induction of T helper cells with specificity for a major epitope and augmentation of protective IgG antibodies in vivo

Abstract: Plasmid DNA-based vaccination is an efficient way to evoke various forms of protective immunity in laboratory animals. Our previous experiments have shown that mice immunized with either plasmid DNA encoding the outer surface lipoprotein A (pOspA) of Borrelia burgdorferi or the respective lipoprotein (Lip-OspA) produce protective antibodies against subsequent challenge with virulent spirochetes. In the present study, we compared the specificity and function of T cells generated in AKR/N mice previously immuniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Direct gene transfer into mouse muscle or skin leads to expression of an immunogenic protein encoded by the injected plasmid and has created a novel technology of immunization designated as nucleic acid or DNA vaccination [1,2]. In experimental animal models injection of a plasmid coding for a single antigenic protein confers protection against viral, protozoal, and more recently, intracellular bacterial infections including influenza virus [3], Plasmodium yoelii [4], Mycobacterium tuberculosis [5,6] and Borrelia burgdorferi [7,8]. Whether DNA vaccination protects against enteropathogenic extracellular bacteria, however, has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Direct gene transfer into mouse muscle or skin leads to expression of an immunogenic protein encoded by the injected plasmid and has created a novel technology of immunization designated as nucleic acid or DNA vaccination [1,2]. In experimental animal models injection of a plasmid coding for a single antigenic protein confers protection against viral, protozoal, and more recently, intracellular bacterial infections including influenza virus [3], Plasmodium yoelii [4], Mycobacterium tuberculosis [5,6] and Borrelia burgdorferi [7,8]. Whether DNA vaccination protects against enteropathogenic extracellular bacteria, however, has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this line, we and others have shown that vaccination with ospA-containing plasmids elicited Ab responses able to prevent subsequent infection (12,20,35). Similarly, immunization of mice with OspC-encoding DNA vaccines resulted in the production of specific Ab in mice, however, with unknown protective potential (28).…”
mentioning
confidence: 73%
“…Hence, T cells seem to be responsible for development of destructive arthritis as opposed to conferring protection from disease [31]. Attempts to map dominant T-helper-cell epitopes of OspA in humans with a variety of HLA.DR alleles [28], as well as in H-2 k mice [32,33], have been reported. Although several T cell epitopes of OspA have been identified [28], the number of patients tested to date is too small to draw conclusions regarding dominant epitopes for particular class II MHC alleles.…”
Section: Review Articlementioning
confidence: 99%
“…Although several T cell epitopes of OspA have been identified [28], the number of patients tested to date is too small to draw conclusions regarding dominant epitopes for particular class II MHC alleles. In the H-2 k mouse, a single, C-terminal peptide is able to prime the animal for a protective anti-OspA antibody response [32,33]. Despite intensive investigations by many research groups, we still do not understand the cellular and molecular mechanisms which lead to antibiotic treatment-resistant Lyme arthritis in certain individuals.…”
Section: Review Articlementioning
confidence: 99%